Biochemistry and Health Benefits of Fatty Acids 2018
DOI: 10.5772/intechopen.81122
|View full text |Cite
|
Sign up to set email alerts
|

Commercial and Therapeutic Potential of Plant-Based Fatty Acids

Abstract: This chapter reviews plant-based fatty acids as well as their methods of production, applications in the industry, and benefits in treatments of cardiovascular and cerebral diseases, besides being a source of food. The fatty acids obtained from vegetable matrices have been acting as alternatives to the use of lipids of animal origin, due to their limitation in relation to the increase in demand. Thus, plants have been investigated in order to act as sources of fatty acids and assist in the supply of such deman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 98 publications
1
1
0
Order By: Relevance
“…Interestingly, TAG-assembly-related genes were highly expressed later on (after 35 days of flowering), which is similar to the lipid triacylglycerol biosynthesis described by Bates et al [91]. Fatty acids play important roles in lipid supply in plants and have valuable medicinal properties for humans [93]. This study made a breakthrough in revealing the genetic and molecular determinants of FAs and TAG synthesis in Perilla.…”
Section: Identification Of Genes Involved In Fatty Acid and Lipid Tri...supporting
confidence: 75%
See 1 more Smart Citation
“…Interestingly, TAG-assembly-related genes were highly expressed later on (after 35 days of flowering), which is similar to the lipid triacylglycerol biosynthesis described by Bates et al [91]. Fatty acids play important roles in lipid supply in plants and have valuable medicinal properties for humans [93]. This study made a breakthrough in revealing the genetic and molecular determinants of FAs and TAG synthesis in Perilla.…”
Section: Identification Of Genes Involved In Fatty Acid and Lipid Tri...supporting
confidence: 75%
“…This study identified twenty-five cis-acting elements according to their functional annotations, which were related to hormone responses and abiotic stress. Notably, the genes contained cis-acting elements related to Fatty acids play important roles in lipid supply in plants and have valuable medicinal properties for humans [93]. This study made a breakthrough in revealing the genetic and molecular determinants of FAs and TAG synthesis in Perilla.…”
Section: Identification Of Genes Involved In Fatty Acid and Lipid Tri...mentioning
confidence: 99%